Edukasi Risiko Delayed Onset Muscle Soreness Akibat Stres Mekanik Pada Aktivitas Olahraga - Prastowo, Bayu; Humairah, Najah Fadiya; Windayati, Aluf Mumtaziah; Yaqub, Lalu Muhammad (Devotion: Journal Corner of Community Service, 2025)
Exercise is becoming increasingly popular, but not without knowing the risks of delayed onset muscle soreness (DOMS). These risks include muscle pain 12 to 72 hours after intense exercise. Lack of knowledge about DOMS often hinders the rehabilitation and recovery process. This service aims to improve the community's understanding and skills in dealing with DOMS through a Community Service (PkM) program with a Participatory Education approach. This program was conducted through lecture and simulation methods to 52 participants in Marong Jamaq Utara Neighborhood, Mataram City, West Nusa Tenggara. The community service results significantly increased participants' understanding of DOMS. The improvement was measured using a pre-test and post-test comparison. Although participants knew that DOMS is a normal condition after exercise, only a few were able to perform proper rehabilitation. Thus, this PkM improved knowledge about DOMS, but further education is needed to enhance practical rehabilitation skills.